سیمایێن کورتە چیرۆکا ژنێ ل دەڤەرا بەهدینان ل بەر روناهیا فیمینیزمێ - HAJI, NAFEESA ISMAIL (Journal of Duhok University, 2023)
The Women’s Short Story in Bahedinan in the light of feminism Since ancient times, women have played a role in the field of writing and literature, and among the Kurdish people, they have also made significant contributions in this field. Many support the view that literature is a human creativity that knows no gender, whether the writer is male or female. On the other hand, there is a contrasting opinion that argues women have their uniqueness, which is reflected in their writings. In this study, we discuss these perspectives and explore their reasons. Additionally, we aim to determine whether Kurdish short stories written by women in Bahdinan exhibit feminist characteristics. The paper also delves into the terminology related to this subject to identify the appropriate term. Consequently, this study examines women’s literature in general and its connection to feminist movements. Furthermore, the research addresses a fundamental topic: "The Role of Women in Kurdish Short Story Writing in Bahdinan." It presents the historical output of women in this field by categorizing it according to stages. Several samples of women’s work were selected and analyzed in the study to identify their characteristics and whether they exhibit traits of feminist literature. As a related theory, the research also discusses feminist criticism, explaining its emergence, themes, and application. It was used along with historical methodology to analyze women’s texts in this study. The paper reached several conclusions, including identifying the first short story written by a woman in Bahdinan and categorizing female authors according to historical periods. It also identifies the features of short stories written by women in the mentioned region.